Perspectives of Midwives and Nurse Practitioners in Kentucky on Exercise Counseling During Pregnancy: A Qualitative Study - Madhawa Perera; Taniya S. Nagpal; Maire M. Blankenship; Danilo V. Tolusso; Jordyn M. Cox; Dilini Prashadika; Mark Schafer; Rachel A. Tinius (SAGE Open Nursing)
Introduction Healthcare professionals are in an optimal position to deliver exercise information to pregnant women, yet previous research suggests this seldom happens. Midwives and nurse practitioners, who may have more time with pregnant women, are particularly well suited for this role. Objectives This qualitative study examined the exercise advice and counseling provided by midwives and nurse practitioners in Kentucky, focusing on the barriers they face. Methods Twenty-one midwives and nurse practitioners were recruited until the sample size reached saturation. A survey with open-ended questions was distributed to potential participants in regional hospitals, universities, and professional associations. The framework method was employed to identify common themes in the responses from participants. Results Five main themes emerged: nature of advice, discussing exercise benefits, safety concerns, barriers to counseling, and suggestions for improvement. Findings revealed that midwives and nurse practitioners recommend moderate exercise, aiming for 150 min weekly, monitoring heart rate for intensity, continuing prepregnancy exercise routines, starting low-intensity exercise during pregnancy such as walking, slowing down as pregnancy advances, and avoiding heavy lifting and vigorous activities. Many midwives and nurse practitioners in our sample took a reactive approach to exercise counseling, providing exercise advice if pregnant women asked questions or if they were at high risk for hypokinetic diseases. It was also observed that midwives and nurse practitioners discussed the maternal benefits of exercise more than the fetal benefits. Only a few nurse practitioners and midwives were content with their counseling, while the majority did not feel their counseling was effective. Conclusions Many midwives and nurse practitioners in Kentucky provided comprehensive and accurate physical activity guidelines to pregnant women. However, there is room for them to improve: proactive counseling should include discussions on fetal benefits and using the “talk test” for exercise intensity. Advising patients to slow down as pregnancy progresses should be reconsidered, and evidence-based guidance on specific exercises should be prioritized.